Do we damage nucleus pulposus tissue while treating cerebrovascular ischemic neurological deficits with nimodipine? (Annals of Medical Research, 2021)
None
Keywords: Annulus Fibrosus; Cytotoxicity; Nimodipine; Nucleus Pulposus; Primary Cell Culture.